A Case of Solitary Well‐Differentiated Papillary Mesothelioma with Invasive Foci in the Pleura. Issue 1 (25th November 2016) - Shimizu, Shigeki; Yoon, Hyung‐Eun; Ito, Norimasa; Tsuji, Taisuke; Funakoshi, Yasunobu; Utsumi, Tomoki; Sakaguchi, Masahiro; Tsujimura, Toru; Kasai, Takahiko; Hiroshima, Kenzo; Matsumura, Akihide
Abstract : Well‐differentiated papillary mesothelioma (WDPM) is a rare, distinct tumor consisting of mesothelial cells with a papillary architecture, bland cytological features, and a tendency toward superficial spread without invasion. Rare cases with superficial invasion are termed WDPM with invasive foci. We report a case of solitary WDPM with invasive foci in the pleura. A 61‐year‐old woman presented with a lung adenocarcinoma. A small papillary lesion measuring 29 × 10 × 8 mm was incidentally found in the parietal pleura during a lobectomy for the lung adenocarcinoma. The fibrovascular core of the small papillary lesion was surrounded by a single layer of cuboidal cells with mild to moderate atypia and large nucleoli. Atypical mesothelial cells focally invaded the submesothelial layer. The cells of the papillary lesion were positive for cytokeratins and mesothelial markers. The Ki67 index was <1 %. The lesion did not show p16 loss on fluorescence in situ hybridization. We could not detect atypical mesothelial cells in the specimen from an extrapleural pneumonectomy. WDPM with invasive foci is prone to multifocality; however, our case represents a solitary case in the pleura.